Cardiac involvement with anti‐mitochondrial antibody‐positive myositis mimicking cardiac sarcoidosis. (11th September 2020) - Kadosaka, Takahide; Tsujinaga, Shingo; Iwano, Hiroyuki; Kamiya, Kiwamu; Nagai, Azusa; Mizuguchi, Yoshifumi; Motoi, Ko; Omote, Kazunori; Nagai, Toshiyuki; Yabe, Ichiro; Anzai, Toshihisa
Abstract: Anti‐mitochondrial antibody (AMA)‐positive myositis is an atypical inflammatory myopathy characterized by chronic progressive respiratory muscle weakness, muscular atrophy, and cardiac involvement. Arrhythmias, cardiomyopathy, and myocarditis have been reported as cardiac manifestations. Herein, we present the first report of a patient diagnosed with having AMA‐positive myositis with cardiac involvement mimicking cardiac sarcoidosis.